Zákonník práce
Úplné znenie zákona č. 65/1965 Zb. (Zákonník práce) v znení zákona č. 88/1968 Zb., zákona č. 153/1969 Zb., zákona č. 153/1969 Zb., zákona č. 100/1970 Zb., zákona č. 20/1975 Zb., zákona č. 72/1982 Zb., zákona č. 98/1987 Zb., zákona č. 188/1988 Zb., zákona č. 3/1991 Zb., zákona č. 297/1991 Zb., zákona č. 231/1992 Zb., zákona č. 264/1992 Zb., zákona č. 10/1993 Z.z., zákona NR SR č. 275/1993 Z.z., zákona NR SR č. 304/1995 Z.z., zákona NR SR č. 90/1996 Z.z., zákona NR SR č. 206/1996 Z.z., zákona NR SR č. 330/1996 Z.z., zákona č. 379/1997 Z.z., zákona NR SR č. 43/1998 Z.z., zákona č. 190/1998 Z.z., zákona č. 297/1999 Z.z., zákona č. 95/2000 Z.z., zákona č. 244/2000 Z.z. a zákona č. 245/2000 Z.z.